Differences in White Blood Cells, Neutrophil-to-Lymphocyte Ratio, Tumor Necrosis Factor-α based on Procalcitonin Level in Community-Acquired Pneumonia Patients - Sutanto, Yusup Subagio; Apriningsih, Hendrastutik; Syaikhu, Akhmad; Siregar, Sihsusetyaningtyas Tiominar (Jurnal Respirologi Indonesia, 2024)
Background: Community-acquired pneumonia (CAP) is a respiratory infectious disease caused by bacteria, viruses, or fungi. Procalcitonin (PCT) levels will rise, especially in bacterial infection. PCT examination in CAP can help to confirm the diagnosis and anticipate complications. CAP is diagnosed by symptoms, vital signs, laboratory tests, and radiographic investigations. Inflammatory biomarkers are required for predicting causative microorganisms, guiding antibiotic therapy, and determining severity. The purpose of this study is to compare NLR, WBC, and TNF-α levels in CAP patients dependent on PCT level.Methods: This was an analytical cross-sectional study involving 43 CAP patients admitted to Universitas Sebelas Maret (UNS) Hospital and Moewardi Regional General Hospital Surakarta between February and March 2023. Patients were separated into two groups based on PCT levels: those with levels ≤0.12 ng/mL and >0.12 ng/mL. All patients provided a blood sample for NLR, WBC, TNF-α, and PCT testing. The independent t-test and Mann-Whitney tests were performed for statistical analysis of two unpaired groups, and the Chi-square or Fisher exact test was utilized for ordinal categorical data. If the value of P<0.05, the result is statistically significant.Results: NLR and TNF-α levels were higher in the PCT group >0.12 ng/mL and statistically significant with a value of P=0.001. WBC levels in the PCT group >0.12 ng/mL were higher, but the difference was not statistically significant (P=0.096).Conclusion: The NLR value, WBC, and TNF-α levels were found to be higher in the group with PCT >0.12 ng/mL.